1995
DOI: 10.1128/aem.61.4.1586-1590.1995
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of calves and adult cattle with Escherichia coli O157:H7

Abstract: Preweaned calves and adult cattle were inoculated with 10 10 CFU of Escherichia coli O157:H7 strain 3081, a calf isolate which produces Shiga-like toxin, to define the magnitude and duration of fecal shedding of E. coli O157:H7 for each age group. Fecal samples of eight of eight, eight of eight, three of eight, and two of eight calves were positive at 2, 7, 14, and 20 weeks, respectively. In contrast, nine of nine, two of nine, and one of nine steers were positive at 2, 7, and 14 weeks, respectively. The magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
172
2
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(206 citation statements)
references
References 30 publications
(39 reference statements)
31
172
2
1
Order By: Relevance
“…Only some of these putative AEEC strains are demonstrably pathogenic, suggesting that the maintenance of the LEE in the wider E. coli population confers a survival advantage. One AEEC strain, the human pathogen EHEC O157:H7, is normally non-pathogenic but persists in a proportion of cattle and sheep (Cray and Moon, 1995;Kudva et al, 1995;Cornick et al, 2000;Wray et al, 2000;Conedera et al, 2001;Cookson et al, 2002a), pigs and possibly other non-human species. The LEEmediated capacity of E coli O157:H7 to adhere to epithelial cells may play a role in its persistence in animals (Gyles, 1998).…”
Section: Attaching-effacing Lesions As a Possible Methods Of Bacterialmentioning
confidence: 99%
“…Only some of these putative AEEC strains are demonstrably pathogenic, suggesting that the maintenance of the LEE in the wider E. coli population confers a survival advantage. One AEEC strain, the human pathogen EHEC O157:H7, is normally non-pathogenic but persists in a proportion of cattle and sheep (Cray and Moon, 1995;Kudva et al, 1995;Cornick et al, 2000;Wray et al, 2000;Conedera et al, 2001;Cookson et al, 2002a), pigs and possibly other non-human species. The LEEmediated capacity of E coli O157:H7 to adhere to epithelial cells may play a role in its persistence in animals (Gyles, 1998).…”
Section: Attaching-effacing Lesions As a Possible Methods Of Bacterialmentioning
confidence: 99%
“…In the second study, 54 A/E lesions were demonstrated in 3-and 5-month-old experimentally infected calves, and the same 12-month-old naturally infected steer as the one reported previously. 53 The identification of the terminal rectum as the principal site for EHEC O157:H7 bacterial colonization and A/E lesion formation may explain why, with few exceptions, 51,55-57 these lesions were not detected in intestinal tissue in studies involving 5-day-old gnotobiotic 58 or conventional neonates and young (2-8-week-old) calves, [59][60][61] or cattle older than this infected with EHEC O157:H7. 60 In only one other study 51 had rectal tissue from an older (in this case 3-4-month-old) inoculated animal been examined, and in only one study had tissue from the rectum from adult cattle been shown to be susceptible to E coli O157:H7induced A/E lesions; and this was in explants, not live animals.…”
Section: Escherichia Coli O157:h7 Infection As a Cause Of Subclinicalmentioning
confidence: 99%
“…53 The identification of the terminal rectum as the principal site for EHEC O157:H7 bacterial colonization and A/E lesion formation may explain why, with few exceptions, 51,55-57 these lesions were not detected in intestinal tissue in studies involving 5-day-old gnotobiotic 58 or conventional neonates and young (2-8-week-old) calves, [59][60][61] or cattle older than this infected with EHEC O157:H7. 60 In only one other study 51 had rectal tissue from an older (in this case 3-4-month-old) inoculated animal been examined, and in only one study had tissue from the rectum from adult cattle been shown to be susceptible to E coli O157:H7induced A/E lesions; and this was in explants, not live animals. 55 Hence, the studies by Naylor and colleagues 53,54 were the first to show A/E lesions in a live, naturally infected adult (12-month-old) bovine, and first to show they were limited to the terminal rectum.…”
Section: Escherichia Coli O157:h7 Infection As a Cause Of Subclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistence between EPEC/EHEC strains and other diarrhoeagenic agents has already been noticed in field studies and may be related to the severity and persistance of diarrhoea in farms [5]. The age of the animal is also important: with strains of serotypes O157:H7 and O26:H11 clinical signs could not be reproduced in calves aged one to two weeks but could be reproduced well in newborn calves [1,6,7,18]. The opposite situation may exist for strains belonging to other serotypes, mimicking the situation of EPEC in rabbits [21,26].…”
Section: Discussionmentioning
confidence: 90%